INTERNAL AUDIT AS A MANAGEMENT AID TOOL IN SUPPORTING SERVICE IMPLEMENTATION AND HUMAN RESOURCES QUALITY - Chaerudin, Abdul Rauf; Zullaiqa, Nabila; Zakiyah, Nadhira (Bina Bangsa International Journal of Business and Management, 2023)
Given the limitations of a leader to control and supervise the activities of agencies led management must delegate some authority to his subordinates. Therefore the constraints that arise in the delivery of information on the activities delegated to subordinates. So it takes a part of the independent nature, referred to as internal audit agency. The problem that arises is whether the internal audit role in improving the implementation of quality of service and human resources. Starting from the above description, the authors are interested in discussing this issue with the initial conclusions as follows: "Internal Audit adequately implemented to improve the implementation of Quality Management (quality of service and human resources) Institutions". Object of study is the Banten Police Agency, the author uses descriptive analytical methods and quantitative analysis. The data collection technique is field research and library research. The data obtained and analyzed by comparing the data obtained with the theory. From the results of this research is that the implementation of internal audit is adequate. This proves the existence of independence, competence, audit program, the audit, a report is generated and follow-up. Then the internal audit also play a role in supporting the implementation of Quality of Service and Human Resources for internal audit verification, evaluation and recommendations for the implementation of Quality of Service and Human Resources). Thus, from the above it can be concluded that the presence of adequate internal audit will improve the implementation of Quality of Service and Human Resources